2021
DOI: 10.5713/ajas.19.0399
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of pregnancy-associated glycoprotein profile in milk for early pregnancy diagnosis in goats

Abstract: Objective: This study was conducted to assess the level of pregnancy-associated glycoprotein (PAG) in whole and skim milk samples, and its suitability for early pregnancy diagnosis in goats.Methods: A two-step sandwich enzyme-linked immunosorbent assay (ELISA) system for estimation of milk PAG was developed and validated, which employed caprine-PAG specific polyclonal antisera. Whole and skim milk samples (n = 210 each) from fifteen multiparous goats were collected on alternate days from d 10 to d 30, and ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…PAGs are also detectable from day 32 after conception in the milk of pregnant goats, while they are almost absent in non-pregnant goats [ 104 ]. A very recent study using ELISA [ 105 ] reported day 26 post-mating as the first time-point for significantly higher milk PAGs’ concentrations and day 37 post-mating as the best suitable time point to detect pregnancy in goats. Doğan and Köse [ 106 ], utilizing the visual PAG-ELISA test, reported that it was able to diagnose pregnancy in goats starting from the 28th day after breeding, but its reliability still needs to be verified, since visual results are subjective.…”
Section: Other Livestock Speciesmentioning
confidence: 99%
“…PAGs are also detectable from day 32 after conception in the milk of pregnant goats, while they are almost absent in non-pregnant goats [ 104 ]. A very recent study using ELISA [ 105 ] reported day 26 post-mating as the first time-point for significantly higher milk PAGs’ concentrations and day 37 post-mating as the best suitable time point to detect pregnancy in goats. Doğan and Köse [ 106 ], utilizing the visual PAG-ELISA test, reported that it was able to diagnose pregnancy in goats starting from the 28th day after breeding, but its reliability still needs to be verified, since visual results are subjective.…”
Section: Other Livestock Speciesmentioning
confidence: 99%
“…During the gestation period, the mononucleate and binucleate cells of the ruminant trophectoderm generate pregnancy-associated glycoproteins (PAGs), which originate from the placenta ( Sousa et al, 2006 ). Around day 18 or day 20 following breading, PAGs can be observed in the serum of pregnant ewes ( Barbato et al, 2009 ) and are a reliable indication of pregnancy among ruminants, such as goats ( Singh et al, 2021 ), sheep ( Akköse et al, 2021 ), and cattle ( Silva et al, 2007 ). Progesterone (P 4 ) is a crucial hormone for determining pregnancy in ewes ( Schneider & Hallford, 1996 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pregnancy-associated glycoproteins (PAG) aresynthesized in the mono-and binucleate cells of the ruminant's trophectoderm (Sousa et al, 2006). PAG can be used for pregnancy diagnosis in ruminants by detecting their presence or concentrations in the maternal blood circulation (Akköse and Cebi-Sen, 2019;Chaves et al, 2017;Silva et al, 2007;Singh et al, 2021). de Carolis et al (2020), reported that the cutoff value of PAG concentrations (radioimmuno assay, RIA-706 and RIA-srPool) are ≥ 1.0 ng/mL in order to distinguish between pregnant and nonpregnant Sarda and Lacaune ewes.…”
Section: Introductionmentioning
confidence: 99%